Effect of Dry Maturation Time and the Curing Composition on Proteins in High Quality Beef - Galina V. Gurinovich; Irina S. Patrakova; Vladislav A. Khrenov (Техника и технология пищевых производств)
Meat quality largely depends on the maturation conditions and natural biochemical processes that affect its taste, aroma, tenderness, and technological properties. Dry maturation and technological processing attract a lot of scientific attention. The research objective was to study the effect of dry maturation time on the physicochemical parameters of high-quality beef, as well as the effect of a new curing mix on the properties of raw materials. The research featured dorsal-lumbar cuts of high-quality beef on maturation days 21 and 40. Matured meat was tested for the main components, the solubility of sarcoplasmic and myofibrillar proteins, the hydrophobicity of myofibrillar proteins, protein oxidation products, and the activity of catalase and peroxidase. The chemical composition was evaluated depending on the dry maturation time using the arbitration method. The solubility of proteins was determined by the calorimetric method with a biuret reagent. The hydrophobicity of myofibrillar proteins was determined by bromophenol blue reaction, and the activity of catalase and peroxidase was determined by standard methods. Proteins were extracted with potassium phosphate buffer (pH 7.2), while myofibrillar proteins were extracted with Tris-HCl and KCl buffers at pH 7.5 and 7.0. The meat samples were deboned and salted using sodium chloride and a combined mix of 70% magnesium chloride and 30% sodium chloride. The solubility of myofibrillar proteins on day 21 increased by 23.95% but decreased by 14.1% by day 40. The solubility of sarcoplasmic proteins decreased continuously (22.10 and 31.12%, respectively). The obtained data matched the hydrophobicity of proteins. Dry maturation initiated protein oxidation, as demonstrated by carbonyl and sulfhydryl groups of myofibrillar proteins on maturation day 40 (27.85 nmol/L and 27.3 µmol/g of protein, respectively). Sodium chloride and its mix increased the extractability of proteins by 5.2 and 6.9% on day 21 and by 6.8 and 10.6% on day 40 but triggered protein oxidation. Muscle proteins of high-quality beef proved functional after 21 days of dry maturation. The new mix with reduced sodium content can be recommended for high-quality dry-aged beef production.